Horseshoe kidney: a case report - S, Naveena; C, Mrudula (International Journal of Research in Medical Sciences, 2017)
The horseshoe kidney was originally regarded as a rare anatomical curiosity, but with the aid of retrograde pyelogram, intravenous urogram and renal arteriograms in this present age of diagnosis, the incidence of horseshoe kidney is estimated at 1 in 200-400 individuals or 1 in 700 autopsies and usually remains asymptomatic. The present report is concerned with a case of horseshoe kidney, which was observed during routine cadaveric dissection, for student education in anatomy dissection hall of Osmania medical college, in a male cadaver. The kidneys formed a U-shaped structure as a result of fusion at the inferior poles of the original kidneys by a parenchymatous isthmus. As a whole, the structure presented a typical horseshoe shape. The location of the kidney was lower than that of the normal kidney. The renal arterial system was almost normal except for a surplus artery into the isthmus that directly originated from the aorta, at the origin of inferior mesenteric artery. Venous drainage of both the kidneys and the isthmus was through two veins which opened independently into the inferior vena cava. The hila on both sides opened towards the ventral direction, and the ureters descended in front of the isthmus and entered the bladder normally. This report is being made because it affords material for a review of embryological and gross anatomy findings in a case of horseshoe kidney, which could help in a thorough urologic evaluation in diagnosed cases prior to any surgical intervention.